FRI0023 Anti-CCP: No Risk Factor for 10-Year Cardiovascular Morbidity in a Large Cohort of Rheumatoid Arthritis Patients. (9th June 2015) - van Maaren, M.C.; Berendsen, M.L.; Arts, E.E.; den Broeder, A.A.; Popa, C.D.; Fransen, J.
Abstract : Background: In rheumatoid arthritis (RA) patients, the incidence of and mortality due to cardiovascular diseases (CVD) is considerably higher than in the general population. The highly RA-specific anticyclic citrullinated protein (anti-CCP), involved in the activation of leukocytes and the proatherogenic status of RA patients (1), is shown to worsen the cardiovascular risk profile (2) . This supports the hypothesis that anti-CCP may be a risk factor for CVD in RA patients (3) . Objectives: We investigated whether anti-CCP status is a risk factor for 10-year cardiovascular morbidity and mortality in RA patients. Methods: This analysis was performed using data from the Nijmegen early RA cohort. Eligible patients were diagnosed with RA according to the ACR 1987or ACR-EULAR 2010 criteria, were Disease-Modifying Anti-Rheumatic Drug (DMARD) naïve, ≥18 years, had a known anti-CCP status and outcome assessment available and had no CVD at baseline or within 0.5 year after study inclusion. Anti-CCP positivity was defined as >40 U/ml. Anti-CCP titers were available in a sub group of patients. Outcomes were defined as having a non-fatal cardiovascular event (morbidity) within 10 years after inclusion or having a fatal cardiovascular event (mortality) within 10 years after inclusion. CVD was defined as physician diagnosed ischemic heart disease, cerebrovascular disease or peripheral artery disease. Patients were censored at their last observation, or at 10 years follow-up. Multivariable Cox proportional hazard models were conducted to compare hazard rate ratios (HR) of 10-year cardiovascular morbidity and mortality between anti-CCP positive and negative patients, corrected for age at baseline, gender and diabetes at baseline. Results: Among the 947 patients included, 631 were anti-CCP positive and 316 anti-CCP negative at baseline. In the anti-CCP positive group, 77 (12.2%) experienced a cardiovascular event, either non-fatal or fatal, within 10 years, compared to 42 (13.3%) in the anti-CCP negative group. This results in a crude 10-year hazard rate ratio (HR) of 0.92[0.63-1.33]. After adjustment for gender, age and diabetes, the HR was 1.18[0.80-1.74]. Seven patients (1.1%) in the anti-CCP positive group, compared to six patients (1.9%) in the anti-CCP negative group, experienced a fatal cardiovascular event within 10 years, resulting in a 10-year mortality HR of 0.59[0.20-1.76]. Also when analyzing anti-CCP titers there was no relation found with CVD. Conclusions: A large effect of anti-CCP status on 10-year cardiovascular morbidity and mortality combined in RA patients could be ruled out. An effect of anti-CCP on one of four CVD outcomes found previously could not be replicated 3 . References: Ogdie A, Yu Y, Haynes K, Love TJ, Maliha S, Jiang Y, et al. Risk of major cardiovascular events in patients with psoriatic arthritis, psoriasis and rheumatoid arthritis: a population-based cohort study. Annals of the rheumatic diseases. 2014. Arnab B, Biswadip G, Arindam P, Shyamash M, Anirban G, Rajan P. Anti-CCP antibody in patients with established rheumatoid arthritis: Does it predict adverse cardiovascular profile? Journal of cardiovascular disease research. 2013;4(2):102-6. Lopez FJ, Min Arro DO, De la Torre I, et al. Association Between Anti–Cyclic Citrullinated Peptide Antibodies and Ischemic Heart Disease in Patients With Rheumatoid Arthritis. 2009;61(4):419–424. Disclosure of Interest: None declared